2001
DOI: 10.1016/s0092-8674(01)00321-x
|View full text |Cite
|
Sign up to set email alerts
|

Subunit-Specific Rules Governing AMPA Receptor Trafficking to Synapses in Hippocampal Pyramidal Neurons

Abstract: AMPA-type glutamate receptors (AMPA-Rs) mediate a majority of excitatory synaptic transmission in the brain. In hippocampus, most AMPA-Rs are hetero-oligomers composed of GluR1/GluR2 or GluR2/GluR3 subunits. Here we show that these AMPA-R forms display different synaptic delivery mechanisms. GluR1/GluR2 receptors are added to synapses during plasticity; this requires interactions between GluR1 and group I PDZ domain proteins. In contrast, GluR2/GluR3 receptors replace existing synaptic receptors continuously; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

79
1,032
11
7

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,012 publications
(1,129 citation statements)
references
References 75 publications
79
1,032
11
7
Order By: Relevance
“…Consistent with these findings, in the current study, chronic nicotine SA increased GluR2/3 subunit levels by 30% in VTA. This finding suggests that there might be a larger pool of recycling GluR2/3 subunits in VTA neurons since these subunits are known to recycle constitutively, which is important for the maintenance of basal synaptic activity (Passafaro et al, 2001;Shi et al, 2001). We also speculate that the AMPA/NMDA EPSC ratio may be increased if more GluR2/3 subunits reside in the plasma membrane.…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with these findings, in the current study, chronic nicotine SA increased GluR2/3 subunit levels by 30% in VTA. This finding suggests that there might be a larger pool of recycling GluR2/3 subunits in VTA neurons since these subunits are known to recycle constitutively, which is important for the maintenance of basal synaptic activity (Passafaro et al, 2001;Shi et al, 2001). We also speculate that the AMPA/NMDA EPSC ratio may be increased if more GluR2/3 subunits reside in the plasma membrane.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, single cell deletion studies reported that ~80% of synaptic AMPARs in CA1 hippocampal neurons comprise GluA1/GluA2 hetromers 8 . However, other studies of subunit abundance in rat hippocampus and cortex suggest AMPARs comprise mainly heteromers containing GluA1 and GluA2 or GluA2 and GluA3 [8][9][10] with approximately equivalent amounts of each heteromer complex 11 . GluA4, on the other hand is tightly developmentally regulated and is sparsely expressed at glutamatergic synapses in principal neurons in adult brain 12 .…”
Section: Subunit-specific Traffickingmentioning
confidence: 84%
“…This is mediated by CaMKII phosphorylation of GluA1 and interaction with synaptic PDZ domaincontaining proteins that recruit and retain GluA1/GluA2 AMPARs at synapses during induction of long-term potentiation (LTP) 15,16 . Once the GluA1-mediated increase in AMPAR number is established, interactions with GluA2 take over to control constitutive and activity-dependent AMPAR endocytosis, and long-term depression (LTD) 10,17 . This model fits well with the general concept that the differential trafficking of individual subunits plays fundamentally important roles in the regulation of excitatory synapses.…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
“…In addition, the composition in subunits also controls the local movements of glutamate receptors (Shi et al, 2001). Few examples of subunit-specific targeting are well documented for nAChRs.…”
Section: Intracellular Targeting and Receptor Clusteringmentioning
confidence: 99%